2003
DOI: 10.1034/j.1600-079x.2003.00079.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin stimulates the activity of protective antioxidative enzymes in myocardial cells of rats in the course of doxorubicin intoxication

Abstract: The study aimed at determining the effect of melatonin on the activity of protective antioxidative enzymes in the heart and of lipid peroxidation products in the course of intoxication with doxorubicin (DOX). The rats were categorized into four groups, receiving: 0.9% NaCl i.p. (NaCl control); melatonin [20 mg/kg body weight (b.w.)] s.c. (control Mel); DOX (2.5 mg/kg b.w.) i.p.; melatonin plus DOX in doses as above. All the substances were administered once in a week for four consecutive weeks. Homogenates of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 44 publications
2
49
2
Order By: Relevance
“…It has been reported that oral melatonin given to SHR, aged 23-25 weeks for 6 weeks, attenuated the raised blood pressure and also lowered the levels of renal TBARS compared to the untreated SHR controls [30]. Melatonin supplementation has been found to reduce the levels of markers of lipid peroxidation in subjects exposed to oxidative stress [12,13,36] but not in normal control rats [12]. The reason for the difference in the results of this study and the others is not clearly apparent.…”
Section: Discussioncontrasting
confidence: 59%
“…It has been reported that oral melatonin given to SHR, aged 23-25 weeks for 6 weeks, attenuated the raised blood pressure and also lowered the levels of renal TBARS compared to the untreated SHR controls [30]. Melatonin supplementation has been found to reduce the levels of markers of lipid peroxidation in subjects exposed to oxidative stress [12,13,36] but not in normal control rats [12]. The reason for the difference in the results of this study and the others is not clearly apparent.…”
Section: Discussioncontrasting
confidence: 59%
“…In addition to its direct ROS‐scavenging activity, melatonin has been shown to increase the expression of antioxidant enzymes such as MnSOD and catalase [55–58]; we did not observe that melatonin increased the MnSOD and catalase protein levels upon DOX treatment (data not shown). Melatonin also exerts some function through the membrane receptors MT1 and MT2 [11].…”
Section: Discussioncontrasting
confidence: 58%
“…The antioxidative properties of melatonin and its metabolites have been extensively studied and the use of this molecule as a novel neural protector has been widely reported [24–32]. The neuroprotective functions of melatonin are directly attributed to its free radical scavenging ability and indirectly to its positive influence on activating the antioxidative enzyme activities [24, 25, 29, 47].…”
Section: Discussionmentioning
confidence: 99%